Thrombin Augments Vascular Cell-dependent Migration of Human Mast Cells: Role of MGF - Baghestanian, Mehrdad; Hofbauer, Roland; Kress, Hans G; Wojta, Johann; Fabry, Astrid; Binder, Bernd R; Kaun, Christoph; Müller, Michael R; Mehrabi, Mohammad R; Kapiotis, Stylianos; Sengoelge, Gürkan; Ghannadan, Minoo; Lechner, Klaus; Valent, Peter (Thrombosis and Haemostasis, 1997)
Recent data suggest that auricular thrombosis is associated with accumulation of mast cells (MC) in the upper endocardium (where usually no MC reside) and local expression of MGF (mast cell growth factor) (25). In this study, the role of vascular cells, thrombin-activation and MGF, in MC-migration was analyzed. For this purpose, cultured human auricular endocardial cells (HAUEC), umbilical vein endothelial cells (HUVEC) and uterine-(HUTMEC) and skin-derived (HSMEC) microvascular endothelial cells were exposed to thrombin or control medium, and the migration of primary tissue MC (lung, n = 6) and HMC-1 cells (human MC-line) against vascular cells (supernatants) measured. Supernatants (24 h) of unstimulated vascular cells (monolayers of endocardium or endothelium) as well as recombinant (rh) MGF induced a significant migratory response in HMC-1 (control: 3025 ± 344 cells [100 ± 11.4%] vs. MGF, 100 ng/ml: 8806 ± 1019 [291 ± 34%] vs. HAUEC: 9703 ± 1506 [320.8 ± 49.8%] vs. HUTMEC: 8950 ± 1857 [295.9 ± 61.4%] vs. HSMEC: 9965 ± 2018 [329.4 ± 66.7%] vs. HUVEC: 9487 ± 1402 [313.6 ± 46.4%], p <0.05) as well as in primary lung MC. Thrombin-activation (5 U/ml, 12 h) of vascular cells led to an augmentation of the directed migration of MC as well as to a hirudin-sensitive increase in MGF synthesis and release. Moreover, a blocking anti-MGF antibody was found to inhibit MC-migration induced by unstimulated or thrombin-activated vascular cells. Together, these data show that endocardial and other vascular cells can induce migration of human MC. This MC-chemotactic signal of the vasculature is associated with expression and release of MGF, augmentable by thrombin, and may play a role in the pathophysiology of (auricular) thrombosis.